Marsalis on music - Marsalis, Wynton 1961- (Norton, 1995)
A manual that uses examples from jazz greats to teach the fundamentals of jazz & the elements of improvisation. Includes a CD.
Keywords: Music; Musik; Music theory -- Elementary works; Practicing (Music)